2014
DOI: 10.6118/jmm.2014.20.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Experience of Menopausal Symptom and Hormone Therapy in Korean Postmenopausal Women

Abstract: ObjectivesTo investigate awareness and experience of menopausal symptom and hormone therapy in Korean postmenopausal women.MethodsA total of 570 postmenopausal women were accepted our survey. The women filled out the questionnaires composed of medical and surgical history, menopausal age and symptom, demand of treatment on menopausal symptom, and personal method for overcoming the symptom. Also, we make inquiries about experience of hormone therapy, concern about hormone therapy, improvement of menopausal symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
2
22
1
Order By: Relevance
“…The results of previous epidemiological studies on the awareness of menopause among Korean menopausal women performed by the Korean Menopause Society101112 are comparable to the results of our study. Although the study population differed among the previous studies and our study, with regard to the number of participants and age groups, the finding that more than half of the participants knew about HT was similar.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of previous epidemiological studies on the awareness of menopause among Korean menopausal women performed by the Korean Menopause Society101112 are comparable to the results of our study. Although the study population differed among the previous studies and our study, with regard to the number of participants and age groups, the finding that more than half of the participants knew about HT was similar.…”
Section: Discussionsupporting
confidence: 90%
“…The present study differs from previous reports1112 by the Korean Menopause Society in several aspects: first, this was the largest study, including over 2300 women, whereas previous studies had 1201 participants. Second, it was the first attempt to utilize a mobile application survey, whereas previous studies were done by face-to-face interviews or answering questionnaires on paper.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…3,7,8 In a Korean study, 49% of postmenopausal women had experienced similar symptoms. 9 Levine et al 10 reported that vulvovaginal symptoms were four times more common in postmenopausal sexually active women. Among them with vulvovaginal symptoms, 40% also had overall sexual dysfunction, 34% arousal difficulties, 24% lack of desire, whereas 19% had orgasm difficulties.…”
Section: Vulvovaginal Symptoms and Sexual Dysfunctionmentioning
confidence: 99%
“…The median age at menopause in Europe ranges from 50.1 to 52.8 years and in Asia from 42.1 to 49.5 years. Among Korean women, common (46.7%) menopausal age was around 46 to 50, but some of them (39%) were 51 to 55 years 2. The population of Mongolia reached 3 million last years with 12% of them being women aged 50 and over.…”
mentioning
confidence: 99%